Presentations (Jamaica Institute of Management KingstonJA, 1990)
Papers deal with issues such as the Caribbean stock market; European Single Market; technological development in the Pacific Basin countries; demands of science and technology on educational policy development; the Jamaican economy; the general consumption tax; and strategic information system vision for Caribbean enterprises.
DC